Reinforcement of concrete structures modern materials are used - Akimkozhaeva M.O. Акимкожаева М.О.; Orazov Zh.G. Оразов Ж.Ғ. (Рroblems of engineering and professional education, 2023)
This article outlines the particular properties. Necessity of reinforcing a concrete reinforcement provided by dividing the structure into three groups. The rules are stored in a particular armatwralandırwda included in the types of materials used. Thus, because of the actual subject of the article will authorize the publication. Currently world-class building products structure, concrete and concrete products is a priority. The main purpose of the development of specific materials, eligible employees to enrich the simple multi-specific materials.